2017
DOI: 10.1021/acscatal.7b03151
|View full text |Cite
|
Sign up to set email alerts
|

Computational Optimization of Electric Fields for Improving Catalysis of a Designed Kemp Eliminase

Abstract: Here we report a computational method to improve efficiency of a de novo designed Kemp Eliminase enzyme KE15, by identifying mutations that enhance electric fields and chemical positioning of the substrate that contribute to free energy stabilization of the transition state.Starting from the design that has a kcat/KM of 27 M -1 s -1 , the most improved variant introduced 4 computationally targeted mutations to yield a kcat/KM of 403 M -1 s -1 , with almost all of the enzyme improvement realized through a 43-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(165 citation statements)
references
References 53 publications
2
160
3
Order By: Relevance
“…8 Markland and co-workers confirmed that the scaffold exerts an overall stabilizing electric field from ab initio molecular dynamics (AIMD) simulations that include Nuclear Quantum Effects (NQE) 16 13,16 ; this is because the electric field calculated in the reactant and transition states are different and cannot be factorized in front of the reaction dipole difference. 8,22 Starting from the original design with a kcat/KM of 27 M -1 s -1 , we created a computationally improved variant through introduction of 4 targeted mutations to yield a kcat/KM of 403 M -1 s -1 .…”
Section: Natural and Synthetic Biocatalysismentioning
confidence: 99%
See 2 more Smart Citations
“…8 Markland and co-workers confirmed that the scaffold exerts an overall stabilizing electric field from ab initio molecular dynamics (AIMD) simulations that include Nuclear Quantum Effects (NQE) 16 13,16 ; this is because the electric field calculated in the reactant and transition states are different and cannot be factorized in front of the reaction dipole difference. 8,22 Starting from the original design with a kcat/KM of 27 M -1 s -1 , we created a computationally improved variant through introduction of 4 targeted mutations to yield a kcat/KM of 403 M -1 s -1 .…”
Section: Natural and Synthetic Biocatalysismentioning
confidence: 99%
“…Shown is the location of the 4 mutations of KE15 best variant (left) and the total electric field contributions to the transition state relative to the original design (right). 22 The positive direction for the bond dipole is the same as for the electric field (from C to H, from N to C and from O to N for the CH, CN and ON bond respectively with magnitude +1 , +0.4 and +2.3 Debye). The efficiency of these computationally designed variants was measured and confirmed experimentally.…”
Section: Natural and Synthetic Biocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The results summarized here may also potentially be relevant to the in silico design [156] of zeolite adsorbents and catalysts, where different zeolite frameworks, could be compared based whether they provide the ideal long-range electrostatic and dispersion interactions, which lead to the most effective stabilization of adsorbed substrates and TSs. In a similar vein, recent studies on electric field optimization in enzymes have emphasized on the importance of electrostatics [157] in the protein scaffolding surrounding the active site, and have even reported computational strategies to improve the efficiency of electric field catalysis in de novo designed Kemp eliminases [158]. Lastly, we note from a theoretical perspective, that Energy Decomposition Analysis (EDA) and Principal Component Analysis (PCA) [118] are promising tools with regards to deconvoluting the contributions of longrange electrostatics and dispersion in selective TS stabilization.…”
Section: Model Detailsmentioning
confidence: 99%
“…[4] The systematic absence of experimentally determinedv alues of Z has likely impeded ar igorous understanding of most chemicalp rocesses in which proteinsa re involved including aggregation and self-assembly, [20][21][22][23][24][25][26] ligand binding, [27][28][29][30][31][32][33][34] catalysis, [35][36][37][38][39] electron transfer, [3,6,[40][41][42][43][44][45][46][47] protein crystallization, [14,48] analytical separation, [49,50] and protein engineering. [51][52][53][54][55][56] It is tempting to assume that the formal net chargeo faprotein predicted from generalized residue pK a values (Z seq )issosimilar to the actual net charge that any difference is irrelevant, and the isoelectric point tells us all we need to know about ap rotein's net charge. Thep K a of individual amino acid residues in folded proteins can vary by severalu nits (possibly as many as 10 units) from textbook values because of solventb urial, dipole-dipole interactions, or metal coordination.…”
Section: Introductionmentioning
confidence: 99%